How to Manage the Fiscal Costs of Natural Disasters - Cevik, Serhan; Huang, Guohua (Washington, D.C. : International Monetary Fund, 2018)
This how-to note focuses on the management of the fiscal costs associated with natural disaster risks. Unlike other types of fiscal risks (for example, unexpected macroeconomic changes or materialization of contingent liabilities), a natural disaster presents a unique challenge to fiscal risk-management and budget processes because of its exogenous nature and potentially overwhelming scale. This note discusses how governments can build fiscal resilience against natural hazards and strengthen fiscal management after a disaster, including through budgeting frameworks and other fiscal policies. The note aims to answer three central questions: How large should fiscal buffers be? How should fiscal buffers be built up? How should fiscal buffers be used efficiently and transparently once a natural disaster has struck? These three questions directly relate to fiscal policy, fiscal risk management, and the budget process-all core areas of IMF expertise. To address them, the note focuses on fiscal strategies for financing recovery efforts and considers approaches to mitigate disaster impact. The note also provides guidance on how to conduct regular risk analyses of natural disasters' potential fiscal consequences and outlines best practices for defining and accounting for the contingent liabilities associated with natural disasters in budgeting frameworks. Finally, the note touches on approaches for risk reduction, disaster risk financing strategies, and risk transfer mechanisms, such as various insurance instruments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet